(untitled) (Scientific Researches in Academia, 2024)
This study investigates gender differences in academic motivation and classroom engagement among 500 university students (250 males and 250 females) in Kathmandu. Using the Student Motivation and Engagement Scale–High School (SMES-HS), it employs descriptive and causal-comparative methodologies to analyze the data. Guided by theories such as Self-Determination Theory, Social Role Theory, and Expectancy-Value Theory, the study examines intrinsic and extrinsic motivation as predictors of engagement. Results reveal significant gender differences, with female students exhibiting higher intrinsic motivation and engagement, while males demonstrate slightly higher extrinsic motivation. Regression analysis highlights academic motivation as a strong predictor of engagement, with gender and academic discipline moderating this relationship. The findings underscore the need for gender-sensitive educational strategies and interventions to foster equitable learning environments. Future research should explore longitudinal designs and diverse cultural contexts to further validate these findings. These insights contribute to improving institutional practices and student support systems.